Benin women cross their palms with silver - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In Benin 98% of palmnut processing is done by village women, showing that post-harvest work can provide a living and thereby help to keep the population in the villages, even though the trend is to migrate to the towns. In Tadokome, in south-west...